Factors Influencing Attitude Toward Organ And Tissue Donation Among Patients In Primary Clinic, Sabah, Malaysia - Kai Joo Lima,; Timothy Tsin Jien Cheng,; Mohammad Saffree Jeffree,; Firdaus Hayati,; Phee Kheng Cheah,; Kuok Ong Nee,; Mohd Yusof Ibrahim,; Shamsul Bahari Shamsudin,; Fredie Robinson,; Khamisah Awang Lukman,; Aza Sherin Mohd Yusuff,; Swe,; et al. (Universiti Sains Islam Malaysia, 2024)
Transplantation Proceedings Volume 52, Issue 3, April 2020, Pages 680-686